Blob-spring model for the dynamics of ring polymer in obstacle environment - Lele, Ashish K.; Iyer, Balaji V. S.; Juvekar, Vinay A. (XVTH International Congress on Rheology - the Society of Rheology 80th Annual Meeting, Pts 1 and 2, 2008)
The dynamical behavior of cyclic macromolecules in a fixed obstacle (FO) environment is very different than the behavior of linear chains in the same topological environment; while the latter relax by a snake-like reptational motion from their chain ends(1) the former can relax only by contour length fluctuations since they are endless.(2) Duke, Obukhov and Rubinstein proposed a scaling model (the DOR model) to interpret the dynamical scaling exponents shown by Monte Carlo simulations of rings in a FO environment.(2) We present a model (blob-spring model) to describe the dynamics of flexible and non-concatenated ring polymer in FO environment based on a theoretical formulation developed for the dynamics of an unentangled fractal polymer.(3) We argue that the perpetual evolution of ring perimeter by the motion of contour segments results in an extra frictional load. Our model predicts self-similar dynamics with scaling exponents for the molecular weight dependence of diffusion coefficient and relaxation times that are in agreement with the scaling model proposed by Obukhov et al.(2).
Keywords: fractal polymer dynamics; linear viscoelasticity; ring polymer dynamics

Gelation of regenerated fibroin solution - Nagarkara, Shailesh; Lele, Ashish K.; Chassenieux, Christophe; Nicolai, Taco; Durand, Dominique (15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, 2008)
Silk fibroin is a high molecular weight multiblock ampiphillic protein known for its ability to form high strength fibers. It is also biocompatible; silk sutures have been traditionally used for many centuries. Recently, there has been much interest in making silk hydrogels for applications ranging from tissue engineering to controlled delivery. Fibroin gels can be formed from aqueous solutions by changing one or more state variables such as pH, temperature and ionic strength. In this work we present our investigations on the gelation of aqueous fibroin solutions derived from Bombyx Mori silk using light scattering, confocal microscopy and rheological techniques.
Keywords: dynamic light scattering; Rheology; silk fibroin gel